Study on Deformation Mechanism and Control Measures of Tanziyan Landslide. (29th March 2022) - Tao, Hai-chuan; Zhang, Yuan; Dong, Jia-xing; Zhou, Zhi-qiang; Gong, Xin-yue; Zhang, Sheng-wei
Abstract : Studying the deformation and failure mechanism of the Tanziyan landslide in Yesanguan Town, Badong County, and designing the controlling measures are of great significance to ensure the sustainable development of urban planning and construction. In this paper, stability of Tanziyan landslide is analyzed using the calculation method of complex plane slip surface. After consideration of the essential characteristics of the disaster body, the deformation and failure mechanism of the landslide is studied, and the corresponding landslide treatment measures are presented. Results show stability state of the landslide is understable to unstable as a whole, and the development process can be roughly divided into three stages: sliding, bending and the cracks are connected. Finally, it is proposed to cut and reshape the slope from the crack groove on the slope top to the national highway, and thenlattice beams and anchor cables are presented to protect the reshaped slope surface. Ecological bags are used to stack and regreen between the lattice structures. A retaining wall is built on the inner side of the national highway at the bottom of the slope cutting area, an active protective net is laid on the east side of the crack groove, and monitoring works are set for potential deformation areas. In short, experiences of engineering practice in this landslidecan provide reference for similar projects.